Effect of Acridine Orange on Pathogenicity of E. coli Isolated from Urinary Tract Infection Patients - Zahraa Shakir Mahmod1 , Ansam Safaa Husen1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
A total of (108) isolate from Urinary tract infection (UTI) patients, only (47) isolate gave a positive result(43.51%) after a number of morphological and biochemical characterization. Our result showed only 28isolate have the ability for protease production and haemolysin production (59.5%), and E. coli no.6 wasthe highest protease production isolate (24mm of lysis area) while the E. coli no.18 was lowest proteaseproduction (12 mm of lysis area). After incubtion on skim milk agar medium at 37°C for 18h and with(100%) haemolysin activity for all 28 isolates after growing on blood agar medium. In our study, firstattempt made on the effect of acridine orange (0.1%) as a curing agent on virulence factors of pathogenicbacteria ( both protease and haemolysin productin) by highly producer E. coli no.6 at concentrations ( 0, 10-1to 10-10) and the results showed that E. coli no.6 loss the protease and haemolysin productin at concentrationof (10-1 to 10-4) while little and normal activities were observed at concentration of (10-5 to 10-10) of acridineorange. Also, this study was investigate the agarose - gel electrophoresis of both cured and normal cells andthe results showed the presence of both chromosomal and plasmid bands in the normal cells and only thepresence of chromosomal band for the cured cells E. coli treated with acridine orange at concentrations of(10-2 to 10-4).